Developing and validating a culturally tailored questionnaire to assess COVID-19 vaccine hesitancy in Israel’s ultraorthodox Jewish population - Imanuel Ber; Wasef Na’amnih; Saritte Perlman; Ben Kasstan; Yehuda Lerman; Khitam Muhsen (Human Vaccines & Immunotherapeutics)
Addressing vaccine hesitancy requires culturally adaptable tools. This study aimed to provide a better understanding of COVID-19 vaccine hesitancy in Israel’s ultraorthodox Jewish community, where vaccine hesitancy is prevalent. We developed and validated a COVID-19 vaccine hesitancy questionnaire and explored correlates of intention to receive the fourth dose of the COVID-19 vaccine in this population. A mixed-methods study employing an exploratory sequential design was conducted in May-September 2022. Building on qualitative data, a questionnaire was developed and validated in a cross-sectional study when the fourth dose was recommended to all adults. Thematic analysis identified several factors influencing COVID-19 vaccine decision-making, predominantly religious authority alongside health information sources, perceived vaccine safety, effectiveness, and trust in state authorities. In the cross-sectional study, 96/106 (90.6%) participants were vaccinated against COVID-19; 5.2%, 25.0%, 65.6%, and 4.2% received 1, 2, 3, and 4 doses, respectively. Intention to receive the fourth dose (yes/maybe) was reported by 46%. A factor analysis yielded several scales expressing perceptions regarding COVID-19, with Cronbach’s Alpha mostly between 0.689 and 0.887. Correlates of intention to receive the fourth dose were age ≥ 50 years: OR = 12.45 (95% CI 1.42–108.93), male-sex: 4.97 (1.47–16.81), perceiving the vaccine as important/effective and safe: 4.11 (1.29–13.13), utilizing ultraorthodox communication channels: 5.86 (1.58–21.73), and the number of previously received doses: 3.14 (1.31–7.53). Complementary evidence emphasized the role of religious authority and information sources (ultraorthodox communication channels) and balancing perceived vaccine safety and effectiveness and disease risk in COVID-19 vaccine hesitancy in Israel’s ultraorthodox Jewish population.